YONO BAKRIE'S HUMOR DISCOURSE PRESUPPOSITION IN STAND UP COMEDY - Nur Santriani Utari Azim (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This study aims to describe the setup and punch line which become humor in stand up comedy and the form of pragmatic involvement in the form of presuppositions contained in the humor presented by Yono Bakrie in Stand Up Comedy Indonesia season X on Kompas TV. This research uses a descriptive method with a qualitative approach. The data sources used in this study are setups, punch lines, and forms of presuppositional pragmatic aspects contained in the humor presented by Yono Bakrie on Stand Up Comedy Indonesia season X on Kompas TV. The data collection technique used in this study was documentation, viewing, and transcription techniques. The data analysis used the theory of Miles and Huberman (2014), which includes the stages of data reduction, data presentation, and conclusion/verification. Based on the findings and research analysis on Yono Bakrie's stand up video, it was known that the supporting factors of the humor studied were found in this humor because it contains set up and punch lines. In contrast, presuppositions were found in the pragmatic aspects of humor, which became one of the supporting aspects of forming a humor.